2024
DOI: 10.3390/microorganisms12030510
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cereal Metagenomics: Unravelling Microbial Communities for Improved Food Security

Kedibone Masenya,
Madira Coutlyne Manganyi,
Tshegofatso Bridget Dikobe

Abstract: Food security is an urgent global challenge, with cereals playing a crucial role in meeting the nutritional requirements of populations worldwide. In recent years, the field of metagenomics has emerged as a powerful tool for studying the microbial communities associated with cereal crops and their impact on plant health and growth. This chapter aims to provide a comprehensive overview of cereal metagenomics and its role in enhancing food security through the exploration of beneficial and pathogenic microbial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 226 publications
0
2
0
Order By: Relevance
“…EpiEffectors, such as zinc finger (ZF), transcription activator-like effector (TALE), or modified CRISPR/Cas9 complexes, such as dead Cas9 (dCas9), are used for targeted epigenome editing, and are often fused with the catalytic domain of epigenetic enzymes for precise modifications (Doddavarapu et al, 2024 ). Active DNA demethylation has been shown to positively affect plant resistance to pathogens such as Pseudomonas syringae (Masenya et al, 2024 ). The proline-alanine-valine (PAV) gene may be associated with specific genomic and epigenomic traits in fungi, offering potential predictive insights into fungal plant pathogen adaptation to hosts and aiding in the development of more effective disease prevention strategies (Joubert and Krasileva, 2024 ).…”
Section: Omics Approaches Mechanism In Beneficial Plant-microbe Inter...mentioning
confidence: 99%
See 1 more Smart Citation
“…EpiEffectors, such as zinc finger (ZF), transcription activator-like effector (TALE), or modified CRISPR/Cas9 complexes, such as dead Cas9 (dCas9), are used for targeted epigenome editing, and are often fused with the catalytic domain of epigenetic enzymes for precise modifications (Doddavarapu et al, 2024 ). Active DNA demethylation has been shown to positively affect plant resistance to pathogens such as Pseudomonas syringae (Masenya et al, 2024 ). The proline-alanine-valine (PAV) gene may be associated with specific genomic and epigenomic traits in fungi, offering potential predictive insights into fungal plant pathogen adaptation to hosts and aiding in the development of more effective disease prevention strategies (Joubert and Krasileva, 2024 ).…”
Section: Omics Approaches Mechanism In Beneficial Plant-microbe Inter...mentioning
confidence: 99%
“…Epigenomic analysis revealed that hypermethylation of xyloglucan endotransglycosylase protein could be influenced by Neobacillus , a dominant and highly abundant species found exclusively in Naxos tubers (Boutsika et al, 2023 ). This integrated approach identifies pivotal microbial taxa, their pathways, and epigenetic markers shaping host-microbe interactions, and offers novel insights into agriculture (Masenya et al, 2024 ).…”
Section: Omics Approaches Mechanism In Beneficial Plant-microbe Inter...mentioning
confidence: 99%